2003
DOI: 10.1172/jci19757
|View full text |Cite|
|
Sign up to set email alerts
|

The adaptive imbalance in base excision–repair enzymes generates microsatellite instability in chronic inflammation

Abstract: Chronic infection and associated inflammation are key contributors to human carcinogenesis. Ulcerative colitis (UC) is an oxyradical overload disease and is characterized by free radical stress and colon cancer proneness. Here we examined tissues from noncancerous colons of ulcerative colitis patients to determine (a) the activity of two base excision-repair enzymes, AAG, the major 3-methyladenine DNA glycosylase, and APE1, the major apurinic site endonuclease; and (b) the prevalence of microsatellite instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
144
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 45 publications
11
144
0
1
Order By: Relevance
“…In support of this notion, Habano et al (2000) found a direct association between alterations in the p53 gene and microsatellite instability in both the nuclear and the mitochondrial genomes. We (Hofseth et al, 2003) and others (Yamada and Farber, 2002) have shown that an adaptive imbalance in BER enzymes can cause microsatellite instability, including during ulcerative colitis, a chronic inflammatory disease. In addition, nitric oxide, which is produced in mitochondria at high levels, can increase 3-methyl Adenine glycosylase activity and cause deamination of cytosine …”
Section: Discussionmentioning
confidence: 86%
“…In support of this notion, Habano et al (2000) found a direct association between alterations in the p53 gene and microsatellite instability in both the nuclear and the mitochondrial genomes. We (Hofseth et al, 2003) and others (Yamada and Farber, 2002) have shown that an adaptive imbalance in BER enzymes can cause microsatellite instability, including during ulcerative colitis, a chronic inflammatory disease. In addition, nitric oxide, which is produced in mitochondria at high levels, can increase 3-methyl Adenine glycosylase activity and cause deamination of cytosine …”
Section: Discussionmentioning
confidence: 86%
“…6,42,43 Furthermore, intracellular-produced free radicals cause direct oxidative DNA damage that may overwhelm the capacity of repair pathways. 42,44 Finally, ROS may induce DNA alterations indirectly by oxidation and inactivation of repair proteins. 6,45 MSI has been mainly associated with cancer 14 or cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that in ulcerative colitis, a chronic inflammatory condition associated with a predisposition to colon cancer, ⑀C levels were higher than in normal colon, whereas ⑀A was lower (62); also, in colon cancer biopsies, the level of ⑀C was 30 times higher than that of ⑀A (63). Recently, it has been shown that inflammation in ulcerative colitis is correlated with an increased level of ANPG, which in turn produces instability at microsatellite sequences in various types of cells in the affected tissue (64). Based on these observations, we propose that abortive repair of LPO-induced ⑀C may have profound biological implications.…”
Section: Discussionmentioning
confidence: 99%